INTEGRASI PENDIDIKAN AGAMA KRISTEN DAN PSIKOLOGI KRISTEN DALAM MEMBENTUK KARAKTER DAN KESEHATAN MENTAL PESERTA DIDIK DI ERA MODERN - Agijimoto Putra Sumule; Agnes Randa Rapang; Fatriana Andale; Adlan Bandolan; Julnita Datu Langi’ (CV. ADIBA AISHA AMIRA, 2026)
The development of life in the modern era brings various challenges to the world of education, particularly in the formation of character and mental health of students. Students not only face increasingly complex academic demands, but also various psychological pressures originating from the social environment, technological developments, and the dynamics of personal life. This condition demands an educational approach that not only emphasizes the cognitive aspect, but also pays attention to the spiritual and psychological dimensions of students. This study aims to examine the integration of Christian Religious Education and Christian psychology in forming character and supporting the mental health of students in the modern era. This study uses a qualitative approach with library research methods through the analysis of various relevant literature sources such as books, scientific journals, and academic documents. The results of the study indicate that the integration of Christian Religious Education and Christian psychology provides a holistic educational approach that takes into account the spiritual, emotional, social, and moral development of students. Christian Religious Education plays a role in instilling the values of faith and morals that shape Christian character, while Christian psychology helps understand the dynamics of students' psychological development and provides an empathetic approach to supporting their mental health.